Behavioural medicine: changing our behaviour. Issue 7539 (23rd February 2006) - Marteau, Theresa; Dieppe, Paul; Foy, Robbie; Kinmonth, Ann-Louise; Schneiderman, Neil
Abstract : A growing body of evidence shows how to make behavioural interventions effective